Επιπολασμός της Legionella spp σε νερά από ξενοδοχειακές μονάδες και νοσοκομεία στην Κύπρο - Τάκη, Αναστασία (Τμήμα Γεωπονικών Επιστημών,Βιοτεχνολογίας και Τεχνολογίας Τροφίμων,Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The Legionella spp is one of bacteria that cause disease (Pontiac fever and Legionnaires' disease). A remarkable point of research throughout the world, due to its high mortality caused by this bacterium in humans. Multiplication in environments where there is water, such as piping, air conditioning systems, fountains, medical equipment, tanks ,hot tubs, etc make it responsible for many cases of Legionellosis. The bacterium can also infect airborne, through inhalation of contaminated with Legionella water droplets. Legionella spp can be in general in all areas where there is water, such as workplaces, entertainment areas, even in our homes where we can inhale droplets of contaminated water. Temperatures between 20°C and 45°C, the biomembrane presence of various microorganisms as well as the stagnation of water are the main factors that favor its growth. In this study data, we will be reviewing matters concerning the causal factor, epidemiology and symptomatology, risk factors, decontamination methods and diagnostic laboratory analyses that are used for the detection of Legionella spp. The ultimate purpose of this paper is to examine the existence of Legionella spp in water distribution circuits of tourist facilities and hospitals in Cyprus, as well as to provide data from the international literature that are documented evidence for the presence and participation of Legionella spp as a causative factor of causing the disease. For conducting this thesis, held control in waters 5 hotel units and 3 hospitals, for detecting Legionella spp. As a general result, of the 100 samples collected, in 40% of the samples were detected with Legionella spp. The Legionella spp was detected in 36% and 42% of water samples collected from hospitals and hotels respectively.
Keywords: Legionella spp; Βacteria; Water; Βακτήρια; Βιομεμβράνη; Νερό